1996
DOI: 10.1111/j.2044-8287.1996.tb00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripartal cognitive impairment: Secondary to depression?

Abstract: Twenty pregnant women and 20 controls matched for age and IQ were tested on a range of cognitive functions at three time points: in the last month of pregnancy, 48 hours after delivery, and four weeks after delivery. Pregnant women obtained significantly lower scores on digit symbol and paced auditory serial addition tests 48 hours after delivery. There were no significant differences between the groups on logical memory, trail making or letter cancellation tasks. The degree of cognitive impairment was correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
4

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 8 publications
(10 reference statements)
2
22
4
Order By: Relevance
“…In the present study, no significant differences were observed between the pregnant women and the nonpregnant women on tasks of visuospatial abilities, although women tended to have lower scores on the Mental Rotations (a spatial task) compared with controls. While there is some inconsistency, most studies found no differences in performance between pregnant women and nonpregnant controls on spatial tasks (Brussé, Duvekot, Jongerling, Steegers, & De Koning, 2008;Eidelman et al, 1993;Glynn, 2010;Sharp et al, 1993).In contrast to previous studies, women in the pregnancy group performed more poorly on a processing speed task compared with the controls (de Groot, et al, 2003;de Groot, et al, 2006;Harris et al, 1996;Vanston & Watson, 2005). A factor that may account for the inconsistency is the use of different time intervals for completion of processing speed tasks.…”
contrasting
confidence: 41%
See 1 more Smart Citation
“…In the present study, no significant differences were observed between the pregnant women and the nonpregnant women on tasks of visuospatial abilities, although women tended to have lower scores on the Mental Rotations (a spatial task) compared with controls. While there is some inconsistency, most studies found no differences in performance between pregnant women and nonpregnant controls on spatial tasks (Brussé, Duvekot, Jongerling, Steegers, & De Koning, 2008;Eidelman et al, 1993;Glynn, 2010;Sharp et al, 1993).In contrast to previous studies, women in the pregnancy group performed more poorly on a processing speed task compared with the controls (de Groot, et al, 2003;de Groot, et al, 2006;Harris et al, 1996;Vanston & Watson, 2005). A factor that may account for the inconsistency is the use of different time intervals for completion of processing speed tasks.…”
contrasting
confidence: 41%
“…For example, impairments on word list learning tasks have been observed during different trimesters and at postpartum (de Groot, Vuurman, Hormstra, & Jolles, 2006; Mickes, Wixted, Sha piro, & Scarff, 2009;Parsons et al, 2004). Furthermore, perfor mance on paragraph recall (Keenan, Yaldoo, Stress, Fuerst, & Ginsburg, 1998), planning (Jarrahi-Zadeh, Kane, Van De Castle, Lachenbruch, & Ewing, 1969), and cognitive speed tasks (Chris tensen, Leach, & Mackinnon, 2010) was worse only in the third trimester.Others have failed to find any differences in scores on objective measures of cognitive functions during pregnancy and postpartum (Casey, 2000;Christensen, Poyser, Pollitt, & Cubis, 1999;Crawley, Dennison, & Carter, 2003;Harris, Deary, Harris Marlene, Lees, & Wilson, 1996;McDowall, 2000), even though participants often reported subjective cognitive difficulties (Christensen et al, 1999;Crawley et al, 2003;McDowall, 2000). It has been suggested that testing in a laboratory setting may underestimate the degree of impairment experienced in day-to-day life (Cuttler, Graf, Pawluski, & Galea, 2011;Rendell & Henry, 2008;).…”
mentioning
confidence: 99%
“…However, the results of studies that have used multi-item questionnaires to assess the frequency of various cognitive failures are contradictory. Gross and Pattison (1995), Keenan et al (1998) and Harris et al (1996), all of whom used different questionnaires, found no difference in the level of reported lapses of memory and concentration between pregnant women and controls, while Casey et al (1999) and Janes et al (1999), using a subset of the Inventory of Memory Experiences Questionnaire reported some differences. Janes et al suggest perceived memory changes may simply be based on a subjective, global impression.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple factors may play into these difficulties, the role of depressive symptoms has found wider support (Buckwalter et al, 2001;Harris et al, 1996;Parsons et al, 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Harris, Deary, Harris, Lees, and Wilson (1996) conducted a study comparing 20 pregnant women to a matched sample of controls. They found differences in selected measures of attention and working memory, which correlated with severity of depression and became nonsignificant when the effect of depression was controlled.…”
Section: Introductionmentioning
confidence: 99%